2014 IEEE Conference on Electrical Insulation and Dielectric Phenomena (CEIDP) 2014
DOI: 10.1109/ceidp.2014.6995729
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of surface discharges in silicone-gel: Prebreakdown discharges in cavities

Abstract: Silicone gel is used to encapsulate power electronic circuits. The weakness of this insulation system is surface discharges which degrade silicone gel. In this paper, various features of surface discharge in gel are evaluated by analyzing the motion of cavities induced by discharges and by measuring dynamic potential distributions of surface discharges in gel. The results indicated that charges accumulated at the cavity surface contribute to retaining the cavity path. Temporal response of the potential at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…This indicates that the conductivity of the cavity near the electrode is high because conducting fragments of molecules accumulate on the cavity surface [29]. The dynamics of the electrical treeing in silicone gels was further explored by measuring the dynamic change of potential distributions during surface discharge at the gelsubstrate interface using the Pockels technique [30,31] where the measured potential directly revealed the amount of accumulated charge on the cavity surface. It was found that when PDs occur, the diameter of voids and the potential close to the cavities fluctuate steeply.…”
Section: Dynamics Of Electrical Treeing In Silicone Gelmentioning
confidence: 99%
“…This indicates that the conductivity of the cavity near the electrode is high because conducting fragments of molecules accumulate on the cavity surface [29]. The dynamics of the electrical treeing in silicone gels was further explored by measuring the dynamic change of potential distributions during surface discharge at the gelsubstrate interface using the Pockels technique [30,31] where the measured potential directly revealed the amount of accumulated charge on the cavity surface. It was found that when PDs occur, the diameter of voids and the potential close to the cavities fluctuate steeply.…”
Section: Dynamics Of Electrical Treeing In Silicone Gelmentioning
confidence: 99%
“…Local high field can induce PDs, and ultimately breakdown. PDs in silicone gel quickly reduce its insulation capabilities due to formation of permanent cavities [1][2][3]. PD measurements carried out with liquids instead of gel [4] evidenced the fact that embedding substrates in a high temperature liquid such as JarythermDBT provides good PD properties at high temperatures, up to 350°C with Alumina substrates, i.e., far higher than the maximum temperature limit of silicone gels.…”
Section: Introductionmentioning
confidence: 99%
“…This causes irreversible degradation of the gel. 7 The presence of moisture in the module can lead to processes such as electrical treeing that can cause failure of the device. 8,9 Changing the encapsulation of the power electronic module to an insulating material with self-healing properties is considered to be more desirable.…”
Section: Introductionmentioning
confidence: 99%
“…These will also serve as a good heat transport medium and prevent electrical discharges in the module. 7 There is also high electric field stress at metallisation along the trench of the IGBT baseplate. These resulted from unipolar switching.…”
Section: Introductionmentioning
confidence: 99%